Design of The Position Consultative Assembly Before and After The Amandement of State Constitution of The Republic Indonesia - Putri, Connie Pania; Flambonita, Suci; Erniwati; Novianti, Diana (Technium Social Sciences Journal, 2021)
Indonesia’s political system changed after the amandment of the state’s constitution. As a consequence, significant changes in the system are inevitable, one of which is the paradigm of its governing body. The amended constitution states that all governing bodies are level, not placing its people’s consultative assembly at the highest position of the people sovereignty manifestation at the fullest. The changes in the state’s governing bodie’s position causes transposition of their tasks and authorities. The previous assembly’s authority, bestowed by the constitution, limits itself into not having regular authority except inaugurating selected president and vice president according to the statutes of the General Election Commission once in five years. Nevertheless, a further discussion may lead to a finding that, in practice, the assembly’s authority is substantively fundamental for Indonesia’s political life. It has the right of amending and ordaining the constitution, for example, which is crucial for the politic since 1945 State Constitution of the Republic of Indonesia is the highest of all laws and regulations.